PENYALURAN BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) DIMASA PANDEMI COVID-19 DI DESA PEWISOA JAYA KABUPATEN KOLAKA - Musdalifah; La Ode Asrun Azis R; Firdaus (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2022)
This study aims to determine the practice of distributing the Village Fund Direct Cash Assistance (BLT-DD) program during the Covid-19 Pandemic in Pewisoa Jaya Village, Tanggetada District, Kolaka Regency. This research is a qualitative descriptive study with data collection methods through interviews, observation and documentation. The results of this study indicate that the implementation of the BLT-DD program during the Covid-19 Pandemic in Pewisoa Jaya Village, Tanggetada District, Kolaka Regency, has not gone well, this can be seen from the determination of the names of Family Cards (KK) as BLT-DD recipients that are not correct. target. In this case, in Pewisoa Jaya Village, there was never any updating of the Integrated Social Welfare Data (DTKS) even though they visited people's homes to collect community data as potential recipients of BLT-DD. The achievement of the objectives of the program policy in Pewisoa Jaya Village has not run optimally, because there are still people who are in the capable category and have received other social assistance but whose names are registered again as BLT-DD recipients, while there are still many poor people who have never been touched by social assistance. so that the objectives of the BLT-DD program have not been fully targeted.